1996
DOI: 10.1002/art.1780390307
|View full text |Cite
|
Sign up to set email alerts
|

Increased bone mass with pamidronate treatment in rheumatoid arthritis. Results of a three‐year randomized, double‐blind trial

Abstract: Objective. Osteoporosis is a frequent complication of rheumatoid arthritis (RA). We therefore investigated the effect of oral pamidronate therapy as a specific bone‐sparing agent in RA. Methods. The study design was a 3‐year randomized, double‐blind trial of 300 mg oral pamidronate/day compared with placebo in 105 RA patients. Bone mineral density (BMD) measured at 12‐month intervals was the primary efficacy parameter. Results. In 3 years, lumbar spine and forearm BMD increased significantly in the pamidronate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(53 citation statements)
references
References 29 publications
2
49
0
2
Order By: Relevance
“…Clinical trials of bisphosphonates in RA generally demonstrated suppressive effects on generalized bone loss but not on focal bone erosions (43)(44)(45)(46). In fact, protection against structural joint damage was reported only with high-dose pamidronate (44).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of bisphosphonates in RA generally demonstrated suppressive effects on generalized bone loss but not on focal bone erosions (43)(44)(45)(46). In fact, protection against structural joint damage was reported only with high-dose pamidronate (44).…”
Section: Discussionmentioning
confidence: 99%
“…At least in animal models, a positive effect in slowing bone erosion was observed, although no full protection could be achieved (9). Moreover, data from human clinical trials that used bisphosphonates for preventing or slowing bone erosion in RA are contradictory (31)(32)(33)(34). However, it should be considered that these agents were added to the DMARD regimens, which modulate disease activity and joint destruction, and that the dose and potency of the agents used were comparably low.…”
Section: Discussionmentioning
confidence: 99%
“…The target sample size was based on an estimated mean Ϯ SD loss of BMD in RA patients of 4.12 Ϯ 6.25% over 2 years (27). To demonstrate a complete inhibition of bone loss by the high-intensity exercise when compared with usual care, and based on 90% power to detect a significant difference (2-sided P ϭ 0.05), a sample size of 48 patients would be required in each study group.…”
Section: Methodsmentioning
confidence: 99%